KAJIAN PENGELOLAAN KAWASAN TAMAN WISATA ALAM (TWA) GUNUNG ASUANSANG KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS PROVINSI KALIMANTAN BARAT - Rino, .; Dirhamsyah, M; Yani, Ahmad (Universitas Tanjungpura, 2016)
Natural Park (TWA) Mount Asuansang an ecological conservation area for the surrounding community. This study examines the extent to which the management and performance BKSDA Western and local governments, which affect the role of the community of the District of Sajingan Sambas district as one of the districts buffer in the management of the Asuansang Gunuug TWA. Results of the analysis showed that the area management TWA Mount Asuansang not maximized, most of this area was originally a logging concession of PT. Yamaker. Object management Nature Park is a policy or authority in the Department of Forestry. The central government set as the Nature Park, the management also by the central government. Regional policy in the management of the TWA simply synergy with BKSDA West. Accessibility to the area is very poor, yet there are facilities and infrastructure in the region, funding management TWA Mount Asuansang by DIPA BKSDA Western sources of funding from the state budget and there has been no cooperation from any party either private or NGO, there has been no public participation in the management area , the problems for local communities manufacture pal area boundary sign on community-owned land around the area. Another thing that the constraints are still there are many community activities in the area of Mount Asuansang TWA. Keywords: Natural Park, Sajingan Large